(untitled) (Stato, Chiese e pluralismo confessionale, 2016)
Corresponding author: F. Arnaboldi, email: farnaboldi@unimi.it. While the paper is the result of intense collaboration between the two authors, sections 3 is attributable to F. Arnaboldi and section 1 and 2 to B. Rossignoli. Section 4 is a joint effort. The authors wish to thank P. Mottura and two anonymous referees for their valuable comments. All errors are ours. Article peer reviewed. SUMMARY: 1. Introduction – 2. Background to anti-money laundering – 3. Financial intermediation, 2011–2014 – 4. Conclusion.